Sero-Prevalence of Toxoplasma Gondii Infection and Associated Risk Factors in Animals Presented to Sholla and Akaki-Kality Veterinary Clinics, Addis Ababa (Global Journal of Medical Research, 2017)
A cross-sectional study on Toxoplasma Gondii in livestock was carried from October 2011 to March 2012 in Addis Ababa, Ethiopia to determine sero-prevalence and associated risk factors. A total 347 serum samples were collected from the jugular veins of each animal and heart of swine, presented veterinary clinics and abattoirs, respectively. The overall prevalence in the six animal species out of 347 animals sampled was 126 (36.1%) which were detected as sero-positive for toxoplasmosis. Prevalence based on animal species, out of 347 different animal species sampled were 71 (36.6%), 15 (37.5%), 11 (25%), 19 (47.5%), 7 (35%) and 3 (33.3%) in ovine, caprine, bovine, swine, equine and camel, respectively. In attempt look for the association between risk factors and sero-prevalence, a questionnaire survey was conducted and the result obtained showed economic loss due to abortion (30%), stillbirth (12%), neonatal mortality (18%), dystocia (17%), retained fetal membrane (8%) and endometritis (6%). Seventy two (72) of the respondents had cats in their household.
Keywords: toxoplasmosis; veterinary clinics; seroprevalence; risk factors